Effects of residue decomposition on productivity and soil fertility in rice-wheat rotation - Yadvinder-Singh; Bijay-Singh; Ladha, J.K.; Khind, C.S.; Khera, T.S.; Bueno, C.S. (Wiley, 2004)
Rice (Oryza sativa L.)–wheat (Triticum aestivum L.) farmers in India burn or remove residues to facilitate seedbed preparation. Incorporation of residues before planting of the next crop generally decreases yields due to N immobilization. Since a window of about 40 d is available between rice harvest and wheat planting, the effect of time of incorporation on rice residue decomposition and N mineralization–immobilization was studied in 1992–1993. The mass loss of residue was 25% for a 10‐d, 35% for a 20‐d, and 51% for a 40‐d decomposition period before wheat planting. Nitrogen release from residue ranged from 6 to 9 kg ha−1 during the wheat season. The immobilization of urea N decreased when residue was allowed to decompose for 10‐d or longer. Based on these studies, a long‐term (1993–2000) experiment was conducted on a sandy loam soil to examine the effect of time of residue incorporation before sowing wheat when compared with burning or removal of residue on yields, N‐use efficiency, and soil fertility. The effect of wheat residue incorporation with green manure (GM, Sesbania cannabina L.) on subsequent rice yields was also determined. Residue incorporation for 10 to 40 d had no effect on wheat yields. Rice yields increased (0.18–0.39 Mg ha−1) when wheat residue was incorporated with GM. Starter N applied at residue incorporation did not influence wheat yields but decreased N recovery efficiency. Physiological efficiency was higher when rice straw was incorporated in wheat and when wheat straw plus GM were incorporated in rice than when rice straw was incorporated for 10 d or when the straw was burned. The long‐term application of rice residue increased C accumulation in soil.